Analysis of factors contributing to medication errors during self-management of medication in the rehabilitation ward: a case control study - Ryohei Suzuki; Takako Uchiya; Ayumi Nakamura; Naoki Okubo; Takamasa Sakai; Masaaki Takahashi; Mariko Kaneko; Ikuko Aiba; Fumiko Ohtsu (BMC, 2022)
Abstract Background In the rehabilitation ward, many elderly patients require continuous use of medication after a stroke or bone fracture, even after discharge. They are encouraged to self-manage their medications from the time of admission. Medication errors, such as a missed dose or incorrect administered medication can worsen conditions, resulting in recurrent strokes, fractures, or adverse effects. The study was aimed to identify risk factors, such as medication and prescription, contributing to errors in self-management of medication. Methods This study was conducted on patients who self-managed their medication in the rehabilitation ward of Higashinagoya National Hospital from April 2018 to March 2020. The patient background including age and sex were investigated. The medication factors examined include the number of medications and administrations per day, dosing frequency on indicated days, prescription and start date are the same, medications from multiple prescriptions, and one package or one tablet at each dosage. The group of medication error cases were defined as the medication error group and that of control cases as the no-medication error group. A logistic regression analysis was performed for factors related to medication errors. Results A total of 348 patients were included in the study, of which 154 patients made medication errors, with 374 total medication error cases. The median number of medications in the medication error group was six, and that in the no-medication error group was five. Statistically significant factors correlated with errors made during self-management of medication were the number of medications, number of administrations per day, dosing frequency on indicated days, and medication from multiple prescriptions. Conclusions When a patient is self-managing their medications, errors are likely to occur due to a high number of medicines they are taking and the complexity of the dosage regimen. Therefore, to prevent medication errors, reviewing the prescribed medications and devise ways to simplify the dosage regimens is crucial.